Visual strategies for managing dental fear and anxiety among individuals with hearing impairment: a systematic review - Olivia, Marceline; Anugerah, Pani Matin; Badruddin, Iwany Amalliah; Bahar, Armasastra; Werdiningsih, Monika; Rahardjo, Anton; Ramadhani, Atik (Padjadjaran Journal of Dentistry, 2025)
ABSTRACTIntroduction: Dental fear and anxiety (DFA) pose significant challenges in treating patients, including individuals with hearing impairments. Visual aids have been reported to be helpful in modifying hearing-impaired people’s behavior. This study aimed to assess the effectiveness of visual strategies in reducing DFA among people with hearing impairments. Methods: A literature search was conducted across five research databases, PubMed, ProQuest, EBSCOhost via Medline, Cochrane, and Scopus, within a restricted publication timeframe. The inclusion criteria were as follows: studies published between 1st January 2013 and 31st July 2024, English language, and primary data studies. We used the PICOS concept, with the population referring to people with hearing impairment and the intervention referring to only a visual strategy to manage DFA. Screening involved eliminating studies that did not meet the eligibility criteria, and the quality of the paper was appraised via validated instruments appropriate for study design, including RoB-2 and ROBINS-I. Data extraction was accomplished by identifying important information such as author, year, study design, key findings and conclusions. Thematic content analysis was performed via ATLAS.ti software. Results: The search identified 133 studies, and a total of six studies were included after the screening process. There were three main themes regarding visual strategies aimed at managing dental anxiety: visual aids (2D and 3D books, VR eyewear, videos with or without eyewear), sign language, and customized educational demonstrations. Good patient-f communication and the application of visual strategies significantly reduce DFA. The strategies were shown to be effective; however, the heterogeneity in the included studies precluded a meaningful meta-analysis. The quality assessment results revealed that only one study had a low risk of bias. Conclusion: Visual strategy play crucial role in managing DFA in hearing-impaired individuals. Further research, particularly involving different age groups and rigorously designed long-term trials is recommended.KEYWORDSHearing impairment, visual aid, dental anxiety, dental fear